Semiautomated On-line for the Determination of Sitagliptin Phosphate using UV-low Pressure Mercury Lamp at 184.9 nm and 253.7 nm at ISNAG-fluorimeter Analyzer - Nagam S. Turkey Al-Awadie (Journal of Global Pharma Technology, 2020)
New methodology for sitagliptin phosphate determination via on-line continuous flow injection manifold design of sitagliptin phosphate-phosphomolybdic acid (PMA) system. The method was applied using continuous flow injection system of a new homemade ISANG -fluorimeter with turbidity measurements at 900 via 2×4 solar cell. Chemical and physical parameters were studied and optimized. The calibration graph was the linear dynamic in the range of (0.1-4.5 mmol.L-1) which was better representation, with correlation coefficient r=0.9965 .The limit of detection (LOD) 35.999µg/sample from the stepwise dilution for the minimum concentration in the linear dynamic ranged of the calibration graph. The method was successfully applied for the determination of sitagliptin phosphate (STP) in two pharmaceuticals preparation of different companies. A comparison was made between the newly developed method analysis with the classical method (UV- spectrophotometry at λ max =267 nm) using the standard addition method via the use of individual and paired t-test and F-test. It was noticed that there was a significant difference between two methods at 95 % confidence level. Keywords: Sitagliptin phosphate, Turbidity, Flow injection analysis. Introduction